Simulation Method for Evaluation of LNG Receiving Terminal Capacity - Dundović, Čedomir; Basch, Danko; Dobrota, Đorđe (Promet - Traffic&Transportation, 2012)
Owing to ever increasing share of the natural gas in the world consumption of the power sources, the international maritime traffic with the liquefied gas is recording constant growth with even greater future anticipations. It results in the need for the construction of new LNG receiving terminals. In order to be integrated in those trends and to make provisions for additional quantities of power sources necessary for its future economic development, the Republic of Croatia is making plans for the construction of such a terminal. Successful planning and designing of LNG terminal depends on the application of appropriate methodology for the evaluation of terminal capacity. This paper gives a simulation method for the evaluation of receiving LNG terminal capacity. KEY WORDS: liquefied natural gas, receiving terminal, evaluation of terminal capacity, model, discrete simulation.